Physician group practice in China's healthcare reform: a national survey on physicians' perspectives and implementation challenges - Rui Fan; Qing Meng; Long Zhang; Chao Liu; Li Han; Meng Liu; Leiyu Shi (Frontiers in Health Services, 2025)
BackgroundThe physician group (PG) model, while well-established in the United States, is a relatively recent healthcare delivery innovation in China. Despite rapid growth in PG registrations, comprehensive understanding of physicians’ perspectives remains limited.ObjectiveTo investigate Chinese physicians’ perspectives and concerns regarding the PG model and identify factors influencing their support for its implementation.MethodsA cross-sectional online survey was conducted among 535 Chinese physicians between October-November 2024. The survey assessed participants’ views on PG advantages, concerns, and overall support. Data analysis included descriptive statistics and variance analyses to explore correlations between physicians’ characteristics and their perspectives.ResultsKey facilitators for PG development included “New career direction outside the existing system” (75.1%) and “Improved income levels” (74.4%). Major concerns comprised “Policies restricting physician mobility” (69.7%) and “Lack of support from hospital managers” (57.8%). Overall support for PGs was moderate (3.710 ± 1.241). Administrative position holders showed significantly higher support than non-administrative staff (p = 0.004), and longer work experience correlated positively with support (p = 0.037). Hospital level and specialty area showed no significant influence on support levels.ConclusionThis first systematic study of Chinese physicians’ perspectives on PGs reveals moderate support driven by career development and income opportunities, while highlighting regulatory and institutional barriers. Results suggest the need for stable policies, enhanced income frameworks, and targeted support for early career physicians-who currently show less support than experienced physicians-to facilitate successful PG implementation in China.